2011
DOI: 10.1111/j.1600-0404.2011.01530.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary Sjogren’s syndrome: cognitive symptoms, mood, and cognitive performance

Abstract: Objective to investigate the relationships between self-reported cognitive abilities, psychological symptoms and neuropsychological outcomes in PSS. Methods PSS patients and healthy controls completed a comprehensive neuropsychometric battery and questionnaires: the Centers for Epidemiological Scale-Depression, the Profile of Fatigue- mental domain (Prof-M) for cognitive symptoms, Fatigue Severity Scale and the Short-Form McGill Pain Questionnaire. Results Female PSS patients (N=39) were similar to control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 31 publications
0
54
1
4
Order By: Relevance
“…Depression is an independent predictor of cognitive symptoms [34], strongly correlates with functional disability [31] and leads to more physician visits and work disability in PSS patients [35]. Strömbeck et al [8] did not find an association between depression and an indirect measure of aerobic capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Depression is an independent predictor of cognitive symptoms [34], strongly correlates with functional disability [31] and leads to more physician visits and work disability in PSS patients [35]. Strömbeck et al [8] did not find an association between depression and an indirect measure of aerobic capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive functions were tested in six previous studies [38]: in three studies, all patients have been tested [3, 5, 8], and four studies gave details of the cognitive results [35, 8]. In the study of Malinow et al [4], 16 out of 40 patients were tested, and seven were found to have mild cognitive impairment, mainly of attention functions.…”
Section: Discussionmentioning
confidence: 99%
“…Delalande et al reported central nervous system involvement in 56 out of 82 patients (68%) with PSS and neurological manifestations [2]. Cognitive manifestations have been observed in 10–50% of PSS patients [38]. Few studies have described the cognitive pattern of PSS [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…Among the studies that have used neuropsychological tests, Mataró et al 18 , Martinez et al 7 , and Segal et al 19 used extensive batteries composed of approximately nine neuropsychological tests. The present study followed the design of Martinez et al 7 , with slight modifications, such as a reduction of the number of tests.…”
Section: Discussionmentioning
confidence: 99%